FOREIGN BODY IN THE LARYNx IN THE THREE YEAR OLD CHILD - D. M. Mustafaev (Неотложная медицинская помощь)
ABSTRACT. The author presents the clinical case — the foreign body in the larynx as the chicken bone in the child of three years. Peculiarity of the presented clinical case is the uncommon foreign body in the larynx as the large chicken bone in the three year old child. Despite large size and location of the foreign body the child was breathing through natural airways. The foreign body was removed through the natural way by the direct laryngoscopy, while avoiding complications.